Foundations of Constructivism Philosophy in Classroom Learning - Cecep Sumarna; Heri Gunawan (GoAcademica Research & Publishing, 2022)
The presence of constructivism philosophy brought significant changes in learning in the classroom, especially the paradigm shift in learning, namely the paradigm of teacher centre to the student centre. Students are encouraged to use all of their abilities constructively by building meaning according to their understanding. This has also brought changes in the learning process, where teachers only act as facilitators, mediators and motivators who help active learners with their knowledge. One of the constructivism-based learning models is Contextual Teaching and Learning, which tries to link the material students learn with their real lives to find meaning.